EMU and the euro : how enterprises could approach the changeover (Office for Official Publications of the European Commission LuxembourgLU, 1997)
Reviews preparations for EMU since the Madrid Council and the agreements reached at the European Council held in Dublin in December 1996. Sets out the main challenges facing non-financial enterprises. Reviews how companies could best organize themselves to meet the EMU challenge.
Located in the Office of the Secretary-General